The applicability of ISO household refrigerator-freezer energy test specifications in Malaysia - Masjuki , H.H.; Saidur , Rahman; Choudhury, Imtiaz Ahmed; Mahlia, Teuku Meurah Indra; Ghani, A.K.; Maleque, Md. Abdul (Elsevier Limited, 2001)
This paper presents the possibility of introducing ISO household refrigerator–freezer test standards in Malaysia. An experiment was conducted to investigate the effect of room temperature, door opening, thermostat setting position, relative humidity, and loading on energy consumption of a household refrigerator– freezer. With the experimental data, a multiple regression equation is developed to investigate their combined effect. Finally, energy consumption according to the regression equation with optimum setting conditions is compared with ISO standard test conditions. Our comparison reveals that ISO refrigerator–freezer test standards are applicable with respect to Malaysian climatic conditions and usage patterns.  2001 Elsevier Science Ltd. All rights reserved.